Intermittent fasting in the treatment of type 2 diabetes - Dyńka, Damian; Rodzeń, Łukasz; Rodzeń, Mateusz; Łojko, Dorota; Deptuła, Adam; Grzywacz, Żaneta; Kraszewski, Sebastian; Bartoń, Karolina; Martin, Peter; Deptuła, Anna Małgorzata; Berry, Ken; Unwin, David (Frontiers in Nutrition, 2025)
The increasing prevalence of type 2 diabetes mellitus (T2DM) has inspired researchers to investigate therapies and tools supporting the treatment of this disease. One such tool is intermittent fasting (IF). Given the nature and mechanism of action of IF, it would be logical for it to have a beneficial effect on T2DM patients. This study analyzes the role of IF in the treatment of type 2 diabetes, used alongside standard recommendations, based on the current literature available to the authors. The authors discuss the benefits of IF in T2DM treatment, such as improved glycaemic control, improved insulin sensitivity, facilitated adherence to recommendations, weight reduction, and lower risk of complications. This study covers the results of meta-analyses, systematic reviews, and randomized controlled trials (RCTs) and shows how novel technologies, including continuous glucose monitors and mobile applications, can support the implementation of IF. The importance of safety monitoring is also highlighted, particularly in insulin-treated patients due to the potential risk of hypoglycaemia.